REJUVENATING ORTHODOX MISSIONARISM AMONG THE LAYMEN: THE ROMANIAN ORTHODOX FELLOWSHIP IN INTERWAR TRANSYLVANIA - BILIUȚĂ, Ionuț (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2017)
The paper discusses the interwar activism of Orthodox laymen and the founding of the organization of the Romanian Orthodox Fellowship. By arguing that they subsequently answered to the call of the Transylvanian Orthodox bishops, it addresses how this initiative of Orthodox laity and clergy meant to counterbalance both the Greek-Catholic oriented propaganda in the intellectual milieus and the corrosive influences of modernity, stemming from secular circles. Another aim targeted by the paper is to emphasize that Archbishop Andrei Șaguna’s 19th century reflections about the status of the ecclesiastical collegiality between the clergy and the laymen in the institutional structures of the Orthodox Church received their actual confirmation with the formation of the Romanian Orthodox Fellowship of intellectuals and their theological framework with the theological reflections highlighting the importance of the laity laid by Fr. Liviu Stan (1909-1973).